Stanniectomy Increases Renal Magnesium and Calcium Excretion in Freshwater North American Eels ( Anguilla Rostrata ) - Butler, David G. (Journal of experimental biology, 1993)
The corpuscles of Stannius are linked to the renal transport of magnesium in freshwater North American eels. The urinary magnesium concentration and rate of magnesium excretion increased 3 days after the corpuscles had been removed, a trend which continued throughout a 14 day observation period. There was no overall change in urine flow rates except for a brief 50% reduction 2 days after stanniectomy. Plasma magnesium concentrations drifted downward after stanniectomy. In contrast, plasma calcium concentrations increased significantly within 2 days following stanniectomy and they continued to increase thereafter. Urinary calcium concentrations and the rate of urinary calcium excretion increased 7 days after stanniectomy, implying that the renal response was subject to the increase in plasma calcium concentration: the urine/plasma calcium ratio remained constant. Even though the urinary calcium concentration increased after stanniectomy, the increase in urinary magnesium concentration was proportionally greater.